Penile trauma in the field: a case of power take-off injury managed without hospitalization - Suresh, Sridhar (International Surgery Journal, 2026)
Power take – off injury (PTO) is the commonest mode for male genital injury. PTO injury occurs when a power electrical / mechanical heavy machine pulls victims loose outfit when entangled and rips off with a de-gloving injury of the male genitalia. In this report we have discussed a case of 42-year-old man, working in a paper factory, who came to our clinic with a de-gloving injury of the penis with PTO model and with reported significant blood loss. He was solely managed in our clinic due to financial constraints and non-availability of a valid health insurance. The patient took one month for whole recovery, with preserved sexual and urinary functions.